2018
DOI: 10.1007/s10856-018-6144-3
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of gold nanoparticle-doped electrospun PCL/chitosan nanofibrous scaffolds for nerve tissue engineering

Abstract: In the field of nerve tissue engineering, nanofibrous scaffolds could be a promising candidate when they are incorporated with electrical cues. Unique physico-chemical properties of gold nanoparticles (AuNPs) make them an appropriate component for increasing the conductivity of scaffolds to enhance the electrical signal transfer between neural cells. The aim of this study was fabrication of AuNPs-doped nanofibrous scaffolds for peripheral nerve tissue engineering. Polycaprolactone (PCL)/chitosan mixtures with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Laminin nanofibre‐mixed PCL electrospun scaffolds increased neuron‐like PC12 cell proliferation and adhesion . Gold nanoparticle‐loaded PCL conduits improved the regenerative capacity of nerve injuries . Graphene scaffolds also induced angiogenesis and stimulated neurite extension by improving Schwann cell viability .…”
Section: Introductionmentioning
confidence: 96%
“…Laminin nanofibre‐mixed PCL electrospun scaffolds increased neuron‐like PC12 cell proliferation and adhesion . Gold nanoparticle‐loaded PCL conduits improved the regenerative capacity of nerve injuries . Graphene scaffolds also induced angiogenesis and stimulated neurite extension by improving Schwann cell viability .…”
Section: Introductionmentioning
confidence: 96%
“…They observed that the conductivity of scaffolds was significantly enhanced following the inclusion of gold nanoparticles that in turn promoted attachment and proliferation of Schwann cells compared to PCL/chitosan nanofibrous scaffolds ( Figure 6C-E) [114].…”
Section: Pcl Polymermentioning
confidence: 99%
“…The adhesion of neuronal cells on the CS membranes accelerates the healing rate of the nervous system. In a similar examination, CS fibers exhibited a superior attachment and migration of Schwann cells (SCs) which reconstructed axons to the Bungner bands in the nervous system [77,[110][111][112][113][114][115][116][117]. On the flip side, SCI is a disaster that may result in severe motor, sensory, and functional disorders.…”
Section: Nerve Regenerationmentioning
confidence: 99%